Of hearts and hypertension blazing genetic trails - Christine E. Seidman, lecturer; Richard P. Lifton, lecturer; Howard Hughes Medical Institute (Chevy Chase, MD Howard Hughes Medical Institute, 2006)
Consists of four lectures on the heart, including information on risk factors, advances in diagnostic methods, identifying "disease genes", and genetic factors in hypertension.
Lecture 1. Brave heart : the circle of life / Christine E. Seidman (60:00) -- Lecture 2. Telltale genes : charting human disease / Richard P. Lifton (60:00) -- Lecture 3. Heartbreak : of mutations and maladies / Christine E. Seidman (60:00) -- Lecture 4. The kidney's tale : of salt any hypertension / Richard P. Lifton (60:00)
Howard Hughes Medical Institute holiday lectures on science, December 1998.
Keywords: Heart; Heart -- Diseases; Human genetics; Hypertension; Myocardium -- Diseases; Gene mapping